COMPARATIVE ANALYSIS OF THE KURDISH PROBLEM IN TURKEY AND THE ISSUE OF CHINESE IN MALAYSIA WITHIN THE CONTEXT OF NATION-STATE AND ETHNIC DIFFERENCES - Musa Yavuz Alptekin (International Journal of Organizational Business Excellence, 2019)
In this study, the ethnic problems which are one of the most significant and perhaps the primary structural difficulties and problems of the nation-state and possible solutions will be suggested. Even if it starts with the general information, the focus of this study would be the subject matter which is known as the Southeastern problem in Turkey, yet it has started to be mentioned as the Kurdish problem in the recent years. This study has the purpose of analyzing the mentioned problem in comparison with the Chinese Problem in Malaysia and determining the advantageous and disadvantageous circumstances in each subsection. Based on those determinations, recommendations will be included regarding which dynamics need to be prioritized in realizing a holistic solution process. The comparison will be conducted in thirteen subsections.